2018
DOI: 10.1112/s0010437x18007273
|View full text |Cite
|
Sign up to set email alerts
|

The Manin constant in the semistable case

Abstract: The Manin constant c of an elliptic curve E over Q is the nonzero integer that scales the pullback of a Néron differential under a minimal parametrization φ : X0(N ) Q ։ E into the differential ω f determined by the normalized newform f associated to E. Manin conjectured that c = ±1 for optimal parametrizations, and we prove that in general c | deg(φ) under a minor assumption at 2 and 3 that is not needed for cube-free N or for parametrizations by X1(N ) Q . Since c is supported at the additive reduction prime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…We suppose that the Manin constant of E has to be odd, which will be fully discussed in Section 2. However, we can remove the Manin constant assumption when 4 ∤ C by the recent work of Česnavičius [3]. Moreover, the conjecture that the Manin constant is always ±1 has been proved by Cremona for all optimal elliptic curves of conductor less than 390000 (see [8]).…”
Section: Introductionmentioning
confidence: 99%
“…We suppose that the Manin constant of E has to be odd, which will be fully discussed in Section 2. However, we can remove the Manin constant assumption when 4 ∤ C by the recent work of Česnavičius [3]. Moreover, the conjecture that the Manin constant is always ±1 has been proved by Cremona for all optimal elliptic curves of conductor less than 390000 (see [8]).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, if we write φ ′ : E ′ → E for the isogeny dual to φ, then φ ′ (P ′ ) = 2P = 0. It follows that E ′ (Q q ) [4] contains an element which is not in the kernel of the isogeny φ ′ , and so we must have E ′ (Q q ) [2] necessarily has order 4, contradicting our assumption. This completes the proof.…”
Section: Introductionmentioning
confidence: 83%
“…Note that, if we assume ν E is odd, the theorem gives the lower bound t E (M ) − 1. In fact, it has been shown that ν E is odd for 4 ∤ C by the work of Mazur [13], Abbes-Ullmo [1], Agashe-Ribet-Stein [2] and Česnavičius [4]. In addition, Cremona [10] has shown numerically that ν E is 1 for C ≤ 60000.…”
Section: Introductionmentioning
confidence: 99%
“…We recall that Manin [15] conjectured that if E is a strong Weil curve in the sense that m E is minimal within the isogeny class of E, then c E = 1. See [16,3,2,6] and the references therein.…”
Section: Manin Constant Given An Elliptic Curvementioning
confidence: 99%